Antioxidant And Antibacterial Characteristic Of Kecombrang Extracts (Etlingera elatior) - iglesias, Iglesias; Siregar, Tagor M (Jurnal Teknologi Pangan, 2024)
Kecombrang (Etlingera elatior) is a plant that contains bioactive compounds such as alkaloids, phenolics, flavonoids, triterpenoids, saponins, and glycosides which are beneficial for body health. This research aimed to determine the antioxidant and antibacterial activity of extracts of kecombrang flowers, stems, and tubers. Powder from each part of the kecombrang plant (flowers, tubers, and stems) was extracted with 80% ethanol solvent using the maceration method for 24 hours at room temperature. The chemical compound composition of the selected extracts was determined using the GC-MS method. Kecombrang flower extract has antioxidant activity (IC50) of 34.13 ± 0.86 ppm, total phenolics of 28.38 ± 1.12 mg GAE/g, and total flavonoids of 2.15 ± 0.03 mg QE/g. Tuber extracts had antioxidant activity (IC50) of 35.09 ± 1.1 ppm, total phenolics of 18.79 ± 0.91 mg GAE/g, and total flavonoids of 0.96 ± 0.05 mg QE/g. Meanwhile, stem extract has antioxidant activity (IC50) of 38.35 ± 1.32 ppm, total phenolics of 14.49 ± 0.56 mg GAE/g, and total flavonoids of 0.77 ± 0.03 mg QE/g.  The antibacterial activity assay against E.coli, kecombrang flower extract showed an inhibition zone of 23.08 ± 0.49 mm with a MIC value of 0.53% and MBC 2.14%, tuber extract showed an inhibition zone of 21.87 ± 0.29 mm with a MIC value of 0.51% and an MBC of 2.04%, the stem extract showed an inhibition zone of 9.68 ± 0.35 mm with a MIC value of 0.41% and a MBC of 1.66%. While  the antibacterial activity assay against S.aureus, kecombrang flower extract showed an inhibition zone of 23.97 ± 0.50 mm with a MIC value of 0.63% and MBC 2.50%, tuber extract showed an inhibition zone of 22.86 ± 0.51 mm with a MIC value of 0.40% and MBC 1.58% and the stem extract showed an inhibition zone of 21.65 ± 0.42 mm with a MIC value of 0.54% and MBC 2.17%. The antibacterial activity of the three types of kecombrang extract is classified as strong. The results of GC-MS analysis of kecombrang flower extract showed the presence of the compounds 3-ethyl-2-cyclohexen-1-ol, 1,2-Benzenediol, and 1,4-Benzenediol which are antibacterial, and 2-methoxy-4-vinylphenol which is an antioxidant.